WAR AND VIOLENCE DURING THE MEXICAN INDEPENDENCE REVOLUTION. (Tzintzun, Revista de Estudios Históricos, 2016)
Collective violence is a crucial phenomenon in order to understand the process ofMexican independence and its social dimension. But there is not a comprehensivestudy on the topic because the existing works are partial, due to the particularaspects they analyze or because of the polarized visions with which they attack ordefend independent or royal violence. The purpose of this paper is to approach thetopic of collective violence during the Mexican Independence War, by characterizingthis phenomenon and making the distinction between subversive violence andrepressive violence. After analyzing the two categories, an evaluation of the twocategories and its underlying meaning of violent acts that can be observed is offered.
Keywords: Violence; Mexican Independence War; Insurgency; gachupines (Spaniards); Political assassination; Hidalgo; Morelos